Exploring the intra-varietal diversity in ‘Graciano’, a minority grapevine cultivar with adaptive capacity to climate change - Javier Portu; Elisa Baroja; Luis Rivacoba; Sergio Ibáñez; Javier Tello (Journal of Agriculture and Food Research, 2025)
Climate change urges grape growers and wine producers for implementing a series of adaptation measures. Although cultivar shifting is one of the most effective ways to face current climate change conditions, the rigid regulations of some of the most relevant winemaking regions hinder the introduction of foreign varieties of high adaptive potential. Here, we explored the use of the minority cultivar ‘Graciano’ as a potential substitute of the elite variety ‘Tempranillo Tinto’, widely cultivated in the demarcated winemaking region of Rioja (Spain). The pairwise comparison of phenology, agronomic performance, and oenological potential features of some commercial clones of both varieties indicated that ‘Graciano’ had multiple beneficial traits (such as late phenology, small berry size, and high must acidity) that indicated better suitability to warming conditions. In addition, the characterization of 13 clonal selections prospected in old vineyards of the region revealed some individuals with additional beneficial traits, so of interest for cultivar improvement. Overall, our results emphasized the importance of preserving varietal and clonal diversity, and support the high potential of ‘Graciano’ as an alternative cultivar for high-quality grape and wine production. Its wider cultivation will potentially reduce the sensitivity level of the demarcated winemaking region of Rioja to climate change.